2019
DOI: 10.1093/humupd/dmz005
|View full text |Cite
|
Sign up to set email alerts
|

Endometriosis and nuclear receptors

Abstract: BACKGROUND Endometriosis is recognized as a steroid-dependent disorder; however, the precise roles of nuclear receptors (NRs) in steroid responsiveness and other signaling pathways are not well understood. OBJECTIVE AND RATIONALE Over the past several years, a number of paradigm-shifting breakthroughs have occurred in the area of NRs in endometriosis. We review and clarify new information regarding the mechanisms responsible … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
128
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 170 publications
(140 citation statements)
references
References 185 publications
3
128
0
1
Order By: Relevance
“…In the case of estrogen receptors (ER), there is an increase of isotype ER-β (ESR2) expression associated with hypomethylation of its promoter (24), and a significant reduction of ER-α (ESR1) expression by hypermethylation of its promoter and through direct inhibition by ER-β. In contrast, both progesterone receptor isoforms PR-A and PR-B (PRG) show a decreased expression; in particular, PR-B undergoes a drastic downregulation (mRNA and protein levels), which is mainly due to hypermethylation of the PR-B promoter (25), therefore affecting downstream hormone target genes (26).…”
Section: Introductionmentioning
confidence: 99%
“…In the case of estrogen receptors (ER), there is an increase of isotype ER-β (ESR2) expression associated with hypomethylation of its promoter (24), and a significant reduction of ER-α (ESR1) expression by hypermethylation of its promoter and through direct inhibition by ER-β. In contrast, both progesterone receptor isoforms PR-A and PR-B (PRG) show a decreased expression; in particular, PR-B undergoes a drastic downregulation (mRNA and protein levels), which is mainly due to hypermethylation of the PR-B promoter (25), therefore affecting downstream hormone target genes (26).…”
Section: Introductionmentioning
confidence: 99%
“…While the degree of methylation did not affect the expression changes of ESR2 or PGR genes in endometriosis (15). The latest study of the team of Yilmaz and Bulun demonstrated that endometrial stromal cells, which participate in the inflammatory process, are induced by oestrogen, and play a role in the formation of prostaglandins, revealed an extremely low ratio of ESR1 to ESR2 expression, resulting from an excessive increase in the expression of the latter gene (12). The cells also demonstrated a deficit of PGR protein, which leads to resistance to progesterone and defective retinoid synthesis.…”
Section: Discussionmentioning
confidence: 97%
“…This study aimed to determine whether there were any correlations between the gene expression of ESR2 and CYP19A1 and the incidence of endometriosis. ESR2 and CYP19A1 genes were selected for the study due to their considerable role in hormonal control, in patients with endometriosis, the development of which is largely determined by steroid hormones (10)(11)(12)(13).…”
mentioning
confidence: 99%
“…It has been demonstrated that there are several abnormalities in the intracavitary endometrium and ectopic endometriotic tissue underlying endometriosis progression: inflammation activated by excess estrogen biosynthesis, defective differentiation due to progesterone resistance, dysregulated differentiation of endometrial mesenchymal cells, and abnormal epigenetic marks. Among these, hypoxia and inflammation play an important role in the regulation of the steroidogenic pathway in the development of endometriosis [75,76]. In endometriosis, progesterone and estrogen signaling are disrupted, commonly resulting in progesterone resistance and estrogen dominance [74].…”
Section: Steroidogenic Pathwaymentioning
confidence: 99%
“…As endometriosis is recognized as a steroid-dependent disorder, numerous researchers have investigated the genes of steroid biosynthesis and signaling [17,47,85]. However, the critical genes that confer this steroidogenic transformation have not been defined to date [74,76]. The physiological and pathologic activities of sex steroids are mediated through the estrogen receptor ESR1/ESR2 genes and the PGR gene.…”
Section: Steroidogenic Pathwaymentioning
confidence: 99%